Assessing the Costs of Living with Wildlife in Developing Countries Using Willingness to Pay - Sutton, William R. (2012)
The costs of living with wildlife are assessed using Namibian subsistence farmers' willingness to pay (WTP) for deterrents to attacks on crops and livestock. A utility-theoretic approach jointly estimates household WTP for deterrent programs in two 'currencies': maize and cash. This has a double payoff. Use of a non-cash staple increases respondent comprehension and provides more information about preferences, improving the accuracy of results. The household shadow value of maize is also identified. Significant costs from living with elephants and other types of wildlife are demonstrated. Compensation for farmers may be warranted on equity and efficiency grounds. Uncontrolled domestic cattle generate even higher costs to farmers than wildlife, highlighting the need to clarify property rights among these farmers.